2006
DOI: 10.1074/jbc.m603099200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Interactions within the Set1 Complex and Their Roles in the Regulation of Histone 3 Lysine 4 Methylation

Abstract: Set1 is the catalytic subunit and the central component of the evolutionarily conserved Set1 complex (Set1C) that methylates histone 3 lysine 4 (H3K4). Here we have determined protein/protein interactions within the complex and related the substructure to function. The loss of individual Set1C subunits differentially affects Set1 stability, complex integrity, global H3K4 methylation, and distribution of H3K4 methylation along active genes. The complex requires Set1, Swd1, and Swd3 for integrity, and Set1 amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
194
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(227 citation statements)
references
References 48 publications
29
194
4
Order By: Relevance
“…The two proteins were therefore expressed in strains deleted for individual components of the COMPASS complex, the yeast analogue of mammalian MLL complex that catalyzes H3K4 methylation. The integrity and stability of COMPASS complex requires the heterodimer of Swd1/Swd3 (WD40 repeat protein), the catalytic subunit Set1, and the plant homeodomain finger protein Spp1 (18). As expected, deletion of SET1, SWD1, and SWD3 abolished mono-, di-, and trimethylation at H3K4, whereas deletion of SPP1 had no effect except for a decrease in trimethylation (Fig.…”
Section: Dna Methylation By Murine Methyltransferases Expressed In Yementioning
confidence: 80%
“…The two proteins were therefore expressed in strains deleted for individual components of the COMPASS complex, the yeast analogue of mammalian MLL complex that catalyzes H3K4 methylation. The integrity and stability of COMPASS complex requires the heterodimer of Swd1/Swd3 (WD40 repeat protein), the catalytic subunit Set1, and the plant homeodomain finger protein Spp1 (18). As expected, deletion of SET1, SWD1, and SWD3 abolished mono-, di-, and trimethylation at H3K4, whereas deletion of SPP1 had no effect except for a decrease in trimethylation (Fig.…”
Section: Dna Methylation By Murine Methyltransferases Expressed In Yementioning
confidence: 80%
“…MLL3/MLL4 regulate adipogenesis ) and primarily monomethylate H3K4 (H3K4me1) at both enhancer (Herz et al 2012;Hu et al 2013) and promoter (Cheng et al 2014) regions, while SET1A/B are the primary H3K4 trimethyltransferases (Wu et al 2008). However, despite divergence in catalytic activity and functional roles, enzymes of the KMT2/COMPASS family must assemble into multisubunit complexes to carry out their biological functions.Our molecular understanding of the protein complexes involved in H3K4 methylation stems from the isolation of COMPASS from Saccharomyces cerevisiae (Miller et al 2001;Roguev et al 2001;Krogan et al 2002;Dehe et al 2006). These studies demonstrated that regulatory subunits found within COMPASS and mammalian COMPASS-like complexes play key roles in stabilizing the enzyme and stimulating its methyltransferase activity as well as targeting the protein complex to specific genomic loci (Couture and Skiniotis 2013).…”
mentioning
confidence: 99%
“…Our molecular understanding of the protein complexes involved in H3K4 methylation stems from the isolation of COMPASS from Saccharomyces cerevisiae (Miller et al 2001;Roguev et al 2001;Krogan et al 2002;Dehe et al 2006). These studies demonstrated that regulatory subunits found within COMPASS and mammalian COMPASS-like complexes play key roles in stabilizing the enzyme and stimulating its methyltransferase activity as well as targeting the protein complex to specific genomic loci (Couture and Skiniotis 2013).…”
mentioning
confidence: 99%
“…Using a TAP-tagging approach in combination with strains harboring genetic deletion of COMPASS components, Roguev et al determined that Cps30 and Cps50 remained bound upon deletion of S. cerevisiae (Sc) SET1 but lost interaction with the other COMPASS subunits, suggesting that these two β-propeller domain containing proteins formed a heterodimer. 8 Subsequent studies confirmed that this heterodimer was critical for maintaining global levels of H3K4 mono-di-and trimethylation in vivo, 24,[29][30][31] demonstrating the importance of the global organization of the ScSET1 complex for its function. Similar to the Cps30-Cps50 heterodimer, deletion of ScSET1 resulted in the dissociation of a Cps60-Cps25 heterodimer, 8 thus supporting previous genome wide yeast two-hybrid studies showing that Cps60 and Cps25 stably associated in budding yeast.…”
Section: Subunit Deletion: the First Approach To Dissect Protein Compmentioning
confidence: 85%
“…This is exemplified by the deletion of Cps50 and Cps30 which decreases the overall level of ScSET1. 2,29,31,37 To tackle these problems, in vitro reconstitution of protein complexes with purified components from a homologous or heterologous system, such as baculovirus-infected insect cells, have proven to be well-suited approaches.…”
Section: Protein Complex Reconstitutionmentioning
confidence: 99%